Linear and nonlinear optical properties of trigonal borate crystals K7MIn2-xYbx(B5O10)3 (M = Ca, Sr, Ba; x=0…2) with isolated B5O10 units - Jamous, Ammar Y.; Svetlichnyi, Valerii A.; Kuznetsov, Artem B.; Kokh, Konstantin A.; Kononova, Nadezda G.; Lapin, Ivan N.; Bolatov, Asset; Zholdas, Y. A.; Kokh, Alexander E. (Journal of alloys and compounds)
Noncentrosymmetric borates K7MIn2−xYbx(B5O10)3 (M = Ca, Sr, Ba; x = 0…2) were synthesized by the solid state reaction and the crystals were successfully grown by the top seeded solution growth method using the K2O-B2O3-MF2 flux. According to Rietveld refinement, the crystal structure belongs to the noncentrosymmetric R32 space group. Also, the octahedrally coordinated In atoms are located at wide ranges ∼8 Å which may be promising for phosphor and laser applications. Samples with ytterbium show a characteristic emission band in the range of 950–1050 nm related to the 2F5/2 → 2F7/2 transition of Yb3+ ions that is commonly used for laser generation. IR, Raman and absorption spectra were obtained for the samples as well. The short cut edge of UV absorption, SHG intensity comparable with KDP and low concentration quenching of luminescence suggest that the K7MIn2−xYbx(B5O10)3 borates are promising self-frequency doubling materials.